SOCIAL AND PSYCHOLOGICAL PROBLEMS OF THE ELDERLY IN THE MODERN SOCIETY - Спицька, Ліана (SWorldJournal, 2023)
The problems of the elderly in modern society are usually considered as a consequence of industrialization and urbanization. In turn, it is necessary to consider the following cultural and social factors that determine, firstly, the specifics of the aging